Raphia australis: Acute toxicity, antioxidant capacity and antihypertensive effect in spontaneously hypertensive rats - Charlotte Mungho Tata; Constance Sewani-Rusike; Olukayode O. Aremu; Benedicta Nkeh-Chungag (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: The fruits of R. australis are eaten as snacks in some West and Central African countries. This study was aimed at evaluating the safety, antioxidant capacity and antihypertensive effects of these fruits. Experimental: The acute toxicity of the extract of R. australis extract (RAE) was evaluated through single and short term oral exposure of mice to RAE. Total phenols and flavonoid contents were quantified followed by 1,1‑diphenyl‑2‑picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. Spontaneously hypertensive rats (SHR) were treated with RAE and blood pressure (BP) was measured after once off treatment (phase I) and in the course of 4 weeks treatment (phase II). Results: The LD50 of RAE was greater than 5000 mg/kg. RAE had mild antioxidant capacity and significantly (P<0.001) decreased systolic and diastolic BP in both once off treatment and 4 weeks treatment while decreasing urine output and increasing feces output. Recommended applications/industries: These results indicate that Raphia australis is not toxic and thus is safe for consumption. Pharmaceutically, it has mild antioxidant and significant antihypertensive properties. It also has the ability to improve appetite, increase bulk thus aiding in peristalsis and waste removal.